Analysis of path planning method using artificial potential field in complex urban environment for UAV - Fong, Marcus Kang Jie (Nanyang Technological University, 2022)
This paper presents the analysis of the artificial potential field method for path planning in the construction environment. The parameters of the algorithm are examined to understand how it interacts with and affects the path generated. A geometrical method is also introduced as an alternative approach attempting to tackle the local minima issue faced by the artificial potential field method.